Hypothalamic supramammillary neurons that project to the medial septum modulate wakefulness in mice - Mengru Liang; Tingliang Jian; Jie Tao; Xia Wang; Rui Wang; Wenjun Jin; Qianwei Chen; Jiwei Yao; Zhikai Zhao; Xinyu Yang; Jingyu Xiao; Zhiqi Yang; et al. (Communications Biology, 2023)
Abstract The hypothalamic supramammillary nucleus (SuM) plays a crucial role in controlling wakefulness, but the downstream target regions participating in this control process remain unknown. Here, using circuit-specific fiber photometry and single-neuron electrophysiology together with electroencephalogram, electromyogram and behavioral recordings, we find that approximately half of SuM neurons that project to the medial septum (MS) are wake-active. Optogenetic stimulation of axonal terminals of SuM-MS projection induces a rapid and reliable transition to wakefulness from non-rapid-eye movement or rapid-eye movement sleep, and chemogenetic activation of SuMMS projecting neurons significantly increases wakefulness time and prolongs latency to sleep. Consistently, chemogenetically inhibiting these neurons significantly reduces wakefulness time and latency to sleep. Therefore, these results identify the MS as a functional downstream target of SuM and provide evidence for the modulation of wakefulness by this hypothalamic-septal projection.